PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS DI KELAS V SDN KEDUNG BADAK 2 - Lulu Sri Wahyuni; Elly Sukmanasa; Annisa Nurul Dhiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the low learning outcomes of students in science and science subjects in class V at SDN Kedung Badak 2 with a KKM score of 75. In the pre-cycle, of the 19 students, only 8 students (42.11%) achieved the KKM score so that learning needs to be improved. According to the results of reflection on the pre-cycle, what results in low student learning outcomes is the implementation of inappropriate learning approaches. In cycle I the learning approach applied was the Teaching at The Right Level approach with the Problem Based Learning learning model. This cycle 1 learning process, apart from being able to increase student activity, is also able to improve student learning outcomes. This is evident from the students' scores, 15 students (78.95%) obtained scores reaching the KKM. From this data, the value obtained increased by 36.84%. The score obtained is still considered unsatisfactory, so improvements need to be made in the next stage, namely cycle 2. Improvements in cycle 2 continue to apply the Teaching at The Right Level approach with the Problem Based Learning learning model. The learning process in cycle 2 is increasingly active and the students' understanding of the science and science subject matter is increasing, so that the results at this stage are even better, namely 18 students (94.74%) scored KKM and 1 student (5.26%) got a score less than the KKM. Thus, it is proven that the application of the Teaching at The Right Level approach with the Problem Based Learning learning model can improve student learning outcomes.